BIOCHEMICAL ESTIMATION OF PRIMARY METABOLITES FROM SEMECARPUS ANACARDIUM - SHARMA, ARCHANA; BARMAN, NACHIKETA; MANVI MALWAL (The Bioscan, 2010)
Plants have formed the basis of sophisticated traditional medicine systems that are still in use due to recognition of natural compounds being non-narcotic, with no side effect and easy availability. Screening of metabolites obtained from plants for their pharmacological assay has indeed been the vast source of innumerable therapeutic agents representing molecular diversity engineered by nature. In the present study the primary metabolites (total soluble sugar, starch, lipids, proteins and phenol) of S.anacardium has been estimated from different plant parts viz., stem, roots, leaves and nuts. The observation showed maximum amount of total soluble sugar (56.33 mg/gdw) and proteins (66.34 mg/gdw) in leaves, starch (44.66mg/gdw) in stems and lipids (75.67 mg/ gdw) and phenol (117.33 mg/gdw) in nuts, of S.anacardium as compared to other parts investigated.